1980
DOI: 10.1152/ajpcell.1980.239.3.c75
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic regulation of tight-junction permeability: effect of plant cytokinins

Abstract: The significance of the "leaky" tight junction might be understood better if cells of the epithelial monolayer possessed mechanisms to regulate molecular flow through the junction. To test this possibility, Necturus gallbladder, a representative leaky epithelium, was studied before, during, and after mucosal exposure to plant cytokinins and two other microfilament-active drugs, cytochalasin B and phalloidin. Concomitant with morphological changes in microfilaments, cytokinins induced rapid reversible increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(83 citation statements)
references
References 19 publications
5
76
0
2
Order By: Relevance
“…This conclusion is in keeping with the view that intercellular junction proteins, such as the cadherin-catenin complex, are restrained spatially by linkage through ␣-actinin to the actin cytoskeleton (12). Other cell lines with a similar junctional biochemistry show a reduction in the number of junctional strands after cytochalasin treatment (4,34,42). Our observations do not exclude the formation of transcellular gaps, as opposed to intercellular gaps (37), or the involvement of vesicular-vacuolar organelles (17).…”
Section: Relation Between Filamentous Actin and Endothelial Barrier Isupporting
confidence: 75%
“…This conclusion is in keeping with the view that intercellular junction proteins, such as the cadherin-catenin complex, are restrained spatially by linkage through ␣-actinin to the actin cytoskeleton (12). Other cell lines with a similar junctional biochemistry show a reduction in the number of junctional strands after cytochalasin treatment (4,34,42). Our observations do not exclude the formation of transcellular gaps, as opposed to intercellular gaps (37), or the involvement of vesicular-vacuolar organelles (17).…”
Section: Relation Between Filamentous Actin and Endothelial Barrier Isupporting
confidence: 75%
“…The precise mechanism of macromolecular transport across the plasma-lymph barrier is controversial. One proposed mechanism is endothelial contraction, which results in opening of leaky sites and thus increased protein permeability (33)(34)(35). It has been reported that endothelial contraction is mediated by transformation of intracellular microfilaments, the magnitude of which may be dependent on intracellular cAMP and/or calcium levels (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Moreover, functional studies showed that fungal-derived cytochalasins, which sever actin filaments, were able to disrupt tight junction barrier function and structure. 24 Although one might conclude from these data that tight junctions needed supporting actin filaments to maintain their structural, and therefore functional, integrity, the observation that cytochalasin-induced tight junction disruption was energy-dependent appeared to refute that interpretation. 25 Rather, ultrastructural examination showed that cytochalasin caused the morphological condensation of perijunctional actin, 25 suggesting that cytochalasin-induced severing of actin filaments might cause cytoskeletal contraction that, in turn, led to tight junction disruption.…”
Section: Tight Junctions Are Intimately Related To the Perijunctionalmentioning
confidence: 99%